(x - 4)/2 - (2x + 1)/3 + 2 11/12 = x/6 - 3/4
Răspunsuri la întrebare
Răspuns de
2
Explicație pas cu pas:
Răspuns de
1
SALUT
(x-4)/2 - (2x+1)/3 +2 11/12 = x/6 -3/4
x-4/2 -2x+1/3 + 2 1/2 = x/6 -3/4
x-4/2 -2x+1/3 + 5/2 = x/6 -3/4
6(x-4)-4(2x+1)+30 = 2x-9
6x-24-8x-4+30 = 2x-9
-2x+2 = 2x-9
-2x-2x = -9-2
-4x = -11
x=11/4 ≈ 2,75
EVERGREEN
Alte întrebări interesante
Matematică,
8 ani în urmă
Geografie,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Informatică,
8 ani în urmă
Engleza,
9 ani în urmă
Engleza,
9 ani în urmă